Surface charge-conversion polymeric nanoparticles for photodynamic treatment of urinary tract bacterial infections. (17th November 2015) - Liu, Shijie; Qiao, Shenglin; Li, Lili; Qi, Guobin; Lin, Yaoxin; Qiao, Zengying; Wang, Hao; Shao, Chen
Abstract: Urinary tract infections are typical bacterial infections which result in a number of economic burdens. With increasing antibiotic resistance, it is urgent that new approaches are explored that can eliminate pathogenic bacteria without inducing drug resistance. Antimicrobial photodynamic therapy (PDT) is a new promising tactic. It is a gentle in situ photochemical reaction in which a photosensitizer (PS) generates reactive oxygen species (ROS) under laser irradiation. In this work, we have demonstrated Chlorin e6 (Ce6) encapsulated charge-conversion polymeric nanoparticles (NPs) for efficiently targeting and killing pathogenic bacteria in a weakly acidic urinary tract infection environment. Owing to the surface charge conversion of NPs in an acidic environment, the NPs exhibited enhanced recognition for Gram-positive ( ex. S. aureus ) and Gram-negative ( ex. E. coli ) bacteria due to the charge interaction. Also, those NPs showed significant antibacterial efficacy in vitro with low cytotoxicity. The MIC value of NPs to E. coli is 17.91 μ g ml −1, compared with the free Ce6 value of 29.85 μ g ml −1 . Finally, a mouse acute cystitis model was used to assess the photodynamic therapy effects in urinary tract infections. A significant decline ( P  < 0.05) in bacterial cells between NPs and free Ce6 occurred in urine after photodynamic therapy treatment. And the plated counting results revealed a remarkable bacterial cells drop ( P  < 0.05) in the sacrificed bladder tissue. Above all, this nanotechnology strategy opens a new door for the treatment of urinary tract infections with minimal side effects.